2018
DOI: 10.1007/s00262-017-2112-x
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo-expanded NK cells from blood and ascites of ovarian cancer patients are cytotoxic against autologous primary ovarian cancer cells

Abstract: Ovarian cancer (OC) is the leading cause of gynecological cancer-related death in North America. Most ovarian cancer patients (OCPs) experience disease recurrence after first-line surgery and chemotherapy; thus, there is a need for novel second-line treatments to improve the prognosis of OC. Although peripheral blood-derived NK cells are known for their ability to spontaneously lyse tumour cells without prior sensitization, ascites-derived NK cells (ascites-NK cells) isolated from OCPs exhibit inhibitory pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 42 publications
4
35
0
Order By: Relevance
“…NK cells are highly enriched in the ascites collected from ovarian carcinoma patients but are mostly CD16 − and show a lack of cytotoxic function with diminished IFNγ production. 33,34 Similar changes and dysfunction were reported in NK cells isolated from patients with esophageal squamous cell carcinoma and non-small cell lung carcinoma, particularly in pleural effusion. 38,39 The downregulation of CD16 on NK cells has been shown to be driven by TGFβ and leads to conversion from cytotoxic to a more immunoregulatory phenotype similar to decidual NK cells.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…NK cells are highly enriched in the ascites collected from ovarian carcinoma patients but are mostly CD16 − and show a lack of cytotoxic function with diminished IFNγ production. 33,34 Similar changes and dysfunction were reported in NK cells isolated from patients with esophageal squamous cell carcinoma and non-small cell lung carcinoma, particularly in pleural effusion. 38,39 The downregulation of CD16 on NK cells has been shown to be driven by TGFβ and leads to conversion from cytotoxic to a more immunoregulatory phenotype similar to decidual NK cells.…”
Section: Discussionsupporting
confidence: 53%
“…Loss of CD16 expression has been reported on NK cells recovered from ovarian patient ascites and was connected to loss of cytotoxic function. 33,34 Interestingly, NK cells from animals treated with anti-PD-L1 also had greater frequencies of CD57 + NK cells (30 vs . 47%, p = 0.0014; Figure 4C) which have been correlated with memory-like phenotype and are associated in several studies with better outcomes and improved long-term survival across many tumor types.…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously reported that OC ascites NK cells have been described to exhibit lower expression of the activating markers NKp30, NKp46, NKG2D and DNAM-1 compared to healthy donor PB-NK cells [ 8 , 49 ]. In our study, we observed the same significantly lower expression of NKp30, NKp46 and DNAM-1 on OC ascites-derived NK cells compared to NK cells from benign peritoneal fluid.…”
Section: Discussionmentioning
confidence: 99%
“…NK cells are capable of exerting anti-tumor activity and lysing tumor cells without prior sensitization in an HLA-unrestricted way in contrast to TILs, for example. It has been shown that it is possible to generate cytotoxic NK cells from the ascites of ovarian cancer patients 35. Clinical experiences are so far limited with low partial response and short duration of PFS 36…”
Section: Cell-based Therapymentioning
confidence: 99%